2015
DOI: 10.1002/jbm.b.33505
|View full text |Cite
|
Sign up to set email alerts
|

Novel biodegradable calcium phosphate/polymer composite coating with adjustable mechanical properties formed by hydrothermal process for corrosion protection of magnesium substrate

Abstract: Ceramic type coatings on metallic implants, such as calcium phosphate (Ca-P), are generally stiff and brittle, potentially leading to the early failure of the bone-implant interface. To reduce material brittleness, polyacrylic acid and carboxymethyl cellulose were used in this study to deposit two types of novel Ca-P/polymer composite coatings on AZ31 magnesium alloy using a one-step hydrothermal process. X-ray diffraction and scanning electron microscopy showed that the deposited Ca-P crystal phase and morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 57 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that the degradation rate of Mg could be controlled by surface modification technologies such as chemical conversion, hydrothermal treatment, 37 sol–gel method, 38 polymer coatings, plasma spraying, microarc oxidation, 39 magnetron sputtering, and electrochemical deposition. 40 The electrochemical deposition method has the ability to produce coatings on the surface of samples with different shapes at relatively low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the degradation rate of Mg could be controlled by surface modification technologies such as chemical conversion, hydrothermal treatment, 37 sol–gel method, 38 polymer coatings, plasma spraying, microarc oxidation, 39 magnetron sputtering, and electrochemical deposition. 40 The electrochemical deposition method has the ability to produce coatings on the surface of samples with different shapes at relatively low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Red arrows indicate the elapse of time. ( b ) Transmission-mode laser diffraction phase microscopic (DPM) image of Si NMs (∼100 nm-thick) at various times of immersion in phosphate-buffered solution (1 M, pH 7.4) at physiological temperature (37 °C) [ 61 ]. Black arrows indicate the elapse of time.…”
Section: Figurementioning
confidence: 99%
“…[ 28 31 ]), polymer (PGA, PLA, PEO-PCL, PEA-PLLA, PLG, etc. [ 32 ]) and composite (HAp-PCL, F-HAp [ 33 ]) have been used according to the implant requirements. CaP coatings done by ion-beam-assisted deposition or electrochemical and chemical treatment reduce the rate of corrosion, but crystal structure, chemical composition, coating morphology and degradation rates differ.…”
Section: Introductionmentioning
confidence: 99%